2010
DOI: 10.1002/dc.21432
|View full text |Cite
|
Sign up to set email alerts
|

Smear preparation of intracranial lesions: A retrospective study of 306 cases

Abstract: A cytohistological correlation with determination of accuracy rate of smear preparation result was done in a retrospective study of 306 cases of intracranial tumors. Cytomorphology of few new entities of CNS tumors are described. The cytological features and WHO grading of the tumors were described on smear preparation. The cases with discrepancy in cytological and histological diagnosis were reviewed again and a final possible diagnosis on smear preparation which should have been given is discussed. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…In fact, this combined methodology greatly enhanced our cytodiagnostic acumen regarding brain lesions. Most previous investigations utilized H+E (69.2%) [3, 5-7, 9-12, 15, 16, 19-26] , Pap (38.5%) [2-5, 7, 11, 18, 19, 26] , or both (21.4%) [3,5,7,11,19,26] ( Table 3 ). The study authors declared these stains to be beneficial for evaluating subtle degrees of nuclear atypia, nuclear chromatin patterns, and cytoplasmic features such as glial projections [2,4] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, this combined methodology greatly enhanced our cytodiagnostic acumen regarding brain lesions. Most previous investigations utilized H+E (69.2%) [3, 5-7, 9-12, 15, 16, 19-26] , Pap (38.5%) [2-5, 7, 11, 18, 19, 26] , or both (21.4%) [3,5,7,11,19,26] ( Table 3 ). The study authors declared these stains to be beneficial for evaluating subtle degrees of nuclear atypia, nuclear chromatin patterns, and cytoplasmic features such as glial projections [2,4] .…”
Section: Discussionmentioning
confidence: 99%
“…The study authors declared these stains to be beneficial for evaluating subtle degrees of nuclear atypia, nuclear chromatin patterns, and cytoplasmic features such as glial projections [2,4] . Eight studies (30.8%) employed TB [1, 8-11, 13, 17, 24] and 8 used MGG stains [2,4,14,19,20,23,24,26] . Krishnani et al [22] observed that lymphoglandular bodies, a useful aid in the identification of lymphoid tumors, were better appreciated with MGG than with H+E staining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations